Comment: Eruptive syringomas of the neck - Antonio Chuh; Vijay Zawar (Our Dermatology Online, 2014)
We read with admiration the article written by Borik L et al on eruptive syringomas (ES) of the neck [1]. We are convinced, from the clinical and histopathological findings, that syringomas is the most likely diagnosis for the patient concerned, and that the authors have provided that highest quality of care to her. We cast reservations, however, on whether the longitudinal time progression of the lesions warrant the term eruptive to be validly applied here. Specifically, the 25-year-old lady was "admitted to the dermatologist's office with the complaint of a rash and itch on the skin on the anterior neck".